Environmental Legislation of Kazakhstan: Achievements, Problems and Trends - Khamzina, Zhanna A.; Buribayev, Yermek A.; Turlykhankyzy, Kuralay; Kuttygalieva, Anarkhan R.; Kubeyeva, Zulfiya T. (Journal of Environmental Accounting and Management, 2026)
This paper examines the state of Kazakhstan’s environmental legislation after nearly 30 years of development as an independent state. The state of ecological systems is directly related to production and economic activities, as well as the state policy in the field of environmental protection. The main environmental problems of Kazakhstan are: the residence of a significant part of the population in the area of direct influence of harmful production factors, the most influential of which are emissions of pollutants into the air, uneven distribution of fresh water across regions, increase in the volume of production and consumption waste. The approximation of Kazakhstan’s legislation to universal environmental protection standards is difficult, including in terms of the impact of sustainable development goals on the context of environmental legislation. The paper explores the areas in which environmental regulations need to be revised and implemented through adequate legal mechanisms. This document facilitates discussions on improving environmental legal norms in national legislation.